Invasive Species in Nepal: Appraisal of Legal Provisions and Institutional Setup - Karki, Ajay; Paudel, Rajan P (The Initiation, 2014)
Invasive species are top threat to biodiversity because of their negative effects on floral and faunal species, food web, on ecosystems and their habitat. Their inherent capability to adjust in wide range of environmental conditions and spread at higher pace with economic activities like travel, trade and tourism have necessitated a concern for their prevention and protection. This has been recognized by Convention on Biodiversity that calls the contracting parties to prevent introduction and control or eradication of invasive species. Nepal as a signatory to this convention has to take essential legal and managerial actions to abide by the convention. This paper reviews some literatures and existing legal documents dealing with the invasive species management. The paper finds out that there is impact of Mikenia micrantha in Chitwan National Park and it may affect the productivity the area. There are legal provisions and institutional setup at National and local level under different acts, regulations and guidelines that influence the introduction, control and eradication of this species. This paper recommends that the full functioning of these provisions and institutional setup is required to manage the invasive species. DOI: http://dx.doi.org/10.3126/init.v5i0.10261 The Initiation 2013 Vol.5; 121-127